Combinatorial Effect of Fertigation Rate and Scheduling on Tomato Performance under Naturally Ventilated Polyhouse in Indian Humid Sub-Tropics - Sonam Rawat; Lalit Bhatt; Pramod Kumar Singh; Poonam Gautam; Suresh Kumar Maurya; Priyanka; Leo Sabatino; Pradeep Kumar (Agronomy, 2023)
Protected cultivation is a resource-efficient method of crop production, however, at the same time, it is resource intensive. An optimum rate and time of fertilizer application is required in order to maximize crop yield vis-à-vis resource use efficiency. However, these aspects are scarcely studied for tomato under low- and medium-tech greenhouses in Indian humid sub-tropics. In this regard, a two-year study was conducted to assess the effect of four NPK fertilization rates (i.e., 120, 100, 80, and 60% of the recommended dose of fertilizers, RDF) and three fertigation scheduling approaches—fertigation at different stages in different proportions of NPK, along with an additional treatment, i.e., farmers’ practice (soil-based application of recommended NPK) for tomatoes under a naturally ventilated polyhouse. The plant growth attributes, the tomato yield- and quality-related traits, the nutrient (NPK) accumulation by the plants, the water use efficiency (WUE), and economics were studied in response to different fertigation rates and scheduling approaches. These parameters were affected by both the rates of NPK fertilization and their time of application (scheduling) over the different growth stages. Among the different rates and time of fertigation, the recommended dose of fertilizer (100% RDF) (i.e., 300 kg N, 150 kg P2O5, and 150 kg K2O per ha and their scheduling as 15% N, 10% P2O5, and 10% K2O of RDF during 15–45 days after transplanting (P1); 40% N, 40% P2O5, and 40% K2O of RDF during 47–76 DAT (P2); 30% N, 40% P2O5, and 40% K2O of RDF during 77–107 DAT (P3); and 15% N, 10% P2O5, and 10% K2O of RDF during 108–138 DAT (P4)) was found to be the optimum for fruit yield, WUE, and economics of tomato under protected condition.